Frequency of Multi-dimensional COPD Indices and Relation with Disease Activity Markers. (1st August 2013) - García-Rio, Francisco; Soriano, Joan B.; Miravitlles, Marc; Muñoz, Luis; Duran-Tauleria, Enric; Sánchez, Guadalupe; Sobradillo, Victor; Ancochea, Julio
Abstract: Our aim was to describe the population-based distribution of several COPD multi-dimensional indices and to evaluate their relationship with daily physical activity, co-morbidity, health status and systemic inflammatory biomarkers. From a population-based sample of 3, 802 subjects aged 40–80 from the EPI-SCAN study, 382 subjects (10.2%) with a post-bronchodilator FEV1 /FVC<0.7 were identified as COPD. Smoking habits, respiratory symptoms, quality of life, co-morbidities, lung function and inflammatory biomarkers were recorded. Health status and daily physical activity were assessed using the EQ-5D and LCADL questionnaires, respectively. The new GOLD grading and the BODE, ADO, DOSE, modified DOSE, e-BODE, BODEx, CPI, SAFE and HRS indices were determined. A notable dispersion in the total scores was observed, although 83–88% of the COPD patients were classified into the mildest level and 1–3% in the most severe. The SAFE index was the best independent determinant of daily physical activity; the SAFE and ADO indices were associated with presence of co-morbidity; and the SAFE and modified DOSE indices were independently related to health status. The systemic biomarkers showed a less consistent relation with several indices. In a population-based sample of COPD patients, the SAFE index reaches the highest relation with physical activity, co-morbidity and health status.